Analisis Dampak Program Literasi Membaca dan Kunjungan Perpustakaan terhadap Hasil Belajar Siswa MI Tarbiyatul Banin - Adilia Elok Makrifatul ‘Ula; Alfiyah, Alfiyah; Niken Ariyana Putri; Sri Surachmi; Yuni Ratnasari (Pusat Riset dan Inovasi Nasional, 2025)
This study focused on the low reading literacy level of students at MI Tarbiyatul Banin and examined the impact of reading literacy programs and library visits on their learning outcomes. Using a quantitative quasi-experimental design, the research involved 100 students from grades 1 to 6, who were divided into experimental and control groups through random sampling. Data were obtained from literacy ability tests and learning outcome assessments, then were analyzed using t-tests, homogeneity and normality tests, the gain index, and effect size. The findings show that reading literacy programs and library visits have a significantly positive effect on student learning outcomes. These activities not only improve students’ literacy and academic performance but also reflect the principles of humanistic and progressive educational philosophies, which view education as a process of shaping individuals who think critically, acquire meaningful knowledge, and act ethically.”